Carboxylesterase 2a deletion provokes hepatic steatosis and insulin resistance in mice involving impaired diacylglycerol and lysophosphatidylcholine catabolism - Gabriel Chalhoub; Alina Jamnik; Laura Pajed; Stephanie Kolleritsch; Victoria Hois; Antonia Bagaric; Dominik Prem; Anna Tilp; Dagmar Kolb; Heimo Wolinski; Ulrike Taschler; Thomas Züllig; et al. (Elsevier, 2023)
Objective: Hepatic triacylglycerol accumulation and insulin resistance are key features of NAFLD. However, NAFLD development and progression are rather triggered by the aberrant generation of lipid metabolites and signaling molecules including diacylglycerol (DAG) and lysophosphatidylcholine (lysoPC). Recent studies showed decreased expression of carboxylesterase 2 (CES2) in the liver of NASH patients and hepatic DAG accumulation was linked to low CES2 activity in obese individuals. The mouse genome encodes several Ces2 genes with Ces2a showing highest expression in the liver. Herein we investigated the role of mouse Ces2a and human CES2 in lipid metabolism in vivo and in vitro. Methods: Lipid metabolism and insulin signaling were investigated in mice lacking Ces2a and in a human liver cell line upon pharmacological CES2 inhibition. Lipid hydrolytic activities were determined in vivo and from recombinant proteins. Results: Ces2a deficient mice (Ces2a-ko) are obese and feeding a high-fat diet (HFD) provokes severe hepatic steatosis and insulin resistance together with elevated inflammatory and fibrotic gene expression. Lipidomic analysis revealed a marked rise in DAG and lysoPC levels in the liver of Ces2a-ko mice fed HFD. Hepatic lipid accumulation in Ces2a deficiency is linked to lower DAG and lysoPC hydrolytic activities in liver microsomal preparations. Moreover, Ces2a deficiency significantly increases hepatic expression and activity of MGAT1, a PPAR gamma target gene, suggesting aberrant lipid signaling upon Ces2a deficiency. Mechanistically, we found that recombinant Ces2a and CES2 show significant hydrolytic activity towards lysoPC (and DAG) and pharmacological inhibition of CES2 in human HepG2 cells largely phenocopies the lipid metabolic changes present in Ces2a-ko mice including reduced lysoPC and DAG hydrolysis, DAG accumulation and impaired insulin signaling. Conclusions: Ces2a and CES2 are critical players in hepatic lipid signaling likely via the hydrolysis of DAG and lysoPC at the ER.